Student Satisfaction with Hostel facilities: A Case Study of Njala University, Njala Campus, Sierra Leone - Tom Williams, Samuel Maxwell; Osborne, Augustus; Bangura, Camilla; Johnny, Jonathan; Bakarr, Ibrahim A.; Koroma, Alusine Hassan; Saidu, Janet Boynah; Musa, Jonathan Aruna; Fefegula, George Mayeh (European Scientific Journal, ESJ, 2022)
Aim and Scope: The importance of students’ social environments in their day-to-day lives cannot be overstated. The extent to which students are happy in their hostel depends on its facilities’ availability, adequacy, and functionality. A case study of Njala University, Njala campus, was used to determine the amenities provided and the level of satisfaction the students derived from those amenities. Methods: A cross-sectional research design was used to conduct the research through in-field observations and a standardized questionnaire. The study’s sample size was estimated at 482 total students. SPSS version 26.0 was used for the data analysis. Result: The study revealed that 82.0% of the respondents were within the age group 20-29 years, and more than two-thirds (70.7%) of the respondents were living in overcrowded rooms with a population of more than the required number of persons per room; this is attributed to the squatting phenomenon among the hostel occupants with the attendant implications of increasing pressure on the available facilities. Equally, students were reasonably satisfied with hostel facilities such as recreational grounds, security status, Library/ICT, waste management and electricity. Results showed respondents were unhappy with the adequacy and performance of certain facilities such as the drainage system, foam, toilet, water supply, kitchen, room size, laundry, and firefighting device. Conclusion: For student convenience, as enrollment continues to rise, the paper suggests that public-private partnerships be established to fund the construction of other hostels with updated designs and amenities.